Renewable, Non-renewable Energy Consumption and Economic Growth in South Africa: Fresh Evidence from ARDL and Wavelet Coherence Analysis - Phiri, Andrew; Sesoai, Tsepiso (International Journal of Energy Economics and Policy, 2024)
We examine the relationship between renewable, non-renewable energy consumption and GDP growth in South Africa, with the aim of determining which energy source is most compatible with economic development. We investigate these relationships by applying autoregressive distributive lag (ARDL) models, vector autoregressive (VAR)-based causality tests and wavelet coherence analysis to annual time series data spanning 1985-2022. On one hand, the ARDL and causality analysis indicate positive (negative) relationships between non-renewable (renewable) energy and growth, whilst the causality tests show that none of the energy sources granger causes economic growth and only reverse causality exists. On the other hand, the more powerful wavelet analysis provides evidence that non-renewables are sustainable for long-term growth whilst renewables, at best, have short-term effects on growth which are mainly driven by the adoption of the White policy paper and the subsequent energy efficiency policies. Overall, these findings imply that South African energy regulators have not taken strong enough policy measures to induce a structural change in which long-term growth can be dependent on renewable energy.